Husband's Support for Postpartum Mothers (Study of The Mother With Vaginal Birth and Section Caesarea) - Yuniarsih, Vera Rismawati; Rahayuningsih, Faizah Betty (Universitas Muhammadiyah Surakarta, 2022)
Purpose: This study aims to determine the picture of husband support for postpartum mothers with vaginal birth and sectio caesarea.Methodology: This research is quantitative research with a Cross-Sectional approach. The sample of this study is postpartum mothers in the Kartasura Health Center work area in 2022. Purposive sampling with a total sample of 54 postpartum mothers. Data collection used the postpartum social support questionnaire (PSSQ) and analyzed using the Independent T-test.Results: The results of the analysis in this study showed the characteristics of respondents aged 20-41 years, with an average baby born at 39 weeks gestation, high school education as many as 30 respondents (56%), mothers who lived with their husbands as many as 49 respondents (90.7%), did not experience complications of childbirth (88.9%), most multipara mothers were 38 respondents (70.4%). In this study, a statistical value of p = 0.952 was obtained. The sig value (p)>(0.05) means that there is no difference in husband support in mothers who give birth in the normal way and husband support in mothers who give birth in secio caesarea ways.Applications/Originality/Value: The difference between this research and pre-existing research lies in the research respondents, the time of the study, measuring instruments, the literature used, the theory used and the results of the research.